Clinical spectrum of oral and dental conditions in intellectually disabled children attending the district early intervention centre of rural tertiary care hospital in coastal Tamil Nadu - Vijayakumar, V.; Dhakshayani, R. V.; Vidhyashree, M. S.; Chitraleka, K. (International Journal of Contemporary Pediatrics, 2025)
Background: Children with intellectual disabilities (ID) often experience challenges in maintaining oral hygiene due to cognitive, behavioural and environmental factors, making them more vulnerable to dental problems. Understanding the oral health status of this group is essential for planning preventive and therapeutic interventions. Methods: A cross-sectional study was conducted among children aged 2-18 years with ID attending the District Early Intervention Centre (DEIC) in a rural tertiary care hospital in Coastal Tamil Nadu. Oral health was assessed using the DMFT/deft and OHI-S indices and intellectual functioning was evaluated using the Binet Kamat Test of Intelligence. Caregivers provided additional data regarding demographics, medical history, diet and hygiene practices. Results: The study revealed a high prevalence of dental caries, gingival diseases and poor oral hygiene among children with ID, with severity increasing in those with lower IQ levels. Behavioural challenges during dental examinations were frequently observed, which complicated oral health assessments and interventions. Conclusions: The findings underscore the need for early dental screening, routine follow-up, caregiver education and improved access to specialized dental care for children with intellectual disabilities, particularly in rural healthcare settings.